어린이그림책일러스트레이션의 표현형식에 대한 어린이의 선호 분석 - 유동관(Dong-Kwan Yoo) (한국콘텐츠학회 논문지, 11(10), 2011)
This study aims to analyze and compare the difference of preference to realistic and fantastic expressions presented in the illustrations of children's picture books. The subject of this study is set for 52 seven-year-old kindergarten students, including 26 boys and 26 girls, in Cheonan. Two times of researches on their preferences were made on the basis of data collection through individual interviews and self-regulatory questionnaires. A children's picture book, which best demonstrates both realistic and fantastic expressions, was selected as a research tool for such questionnaire from the ones produced and printed within Korea, which either are listed in the Recommended Book List of Children's Book Research Association or received any international award. The result shows that both boys and girls prefer fantastic expressions to realistic ones. It was also found that girls tend to prefer realistic expressions that the boys do. Nevertheless, there definitely was a limitation in thorough analysis by region or age, as they tended to show different responses when they were provided with a picture book with similar theme and story, but different form of expression. 본 연구의 목적은 어린이그림책 일러스트레이션에서 나타나는 사실적 표현과 환상적 표현의 선호도 차이를 비교, 분석하는데 있다. 연구대상은 충청남도 천안에 위치한 유치원생 7세 어린이 52명(남 26명, 여26명)으로 하였으며, 2차에 걸쳐 실시한 선호도 조사는 어린이의 개별면접과 자기기입식 설문지를 통한 자료수집방식을 활용하였다. 설문에 활용한 연구도구는 국내에서 제작, 출판된 어린이그림책 중에서 어린이도서연구회의 추천도서와 국외 수상작 가운데 사실적 표현과 환상적 표현이 잘 나타난 어린이그림책을 활용하였다. 선호도비교에서는 남녀어린이 모두 사실적 표현에 비해 환상적 표현형식을 선호하는 것으로 나타났으며, 여자어린이의 경우 남자어린이보다 사실적 표현을 다소 선호하는 것으로 나타났다. 연구과정에서 지역별, 연령별 어린이들의 선호도 분석 및 동일한 주제나 이야기내용을 바탕으로 서로 다른 표현유형의 그림책을 보았을 때 나타나는 어린이의 반응을 분석하는 데는 한계점이 있었다.